Food colloids, biopolymers and materials - Dickinson, Eric; Vliet, Ton van (Special publication (Royal Society of Chemistry (Great Britain)) ;, 2003)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.